AgroNet: A Decentralized Platform for Collaborative Community-Driven Consultancy for Farmers and Agro Vendors - Mondal, Sayanton; Agar, Zack; Raj Ray; Ganguly, Sreetam; Bhowmick, Rubi; Sethi, Rithwick (Journal of Agricultural Extension Management, 2021)
Indian farmers are consistently plagued by age-old practices, which often prove non-productive, counter-productive, and harmful to the environment. In this modern technological era, farmers need to remain updated about technological advancements and government benefits. Timely, accurate consultancy and instant troubleshooting are non-existent in the Indian agricultural landscape. Farmers are forced to turn up to their peers' advice which can be inaccurate or wait for expert advice from domains in KVKs and Extension Departments in Agro-institutions. This article describes a novel decentralized system that combines the low latency of peer-to-peer consulting and the accuracy of expert-based systems and consulting from domain experts as an Android portal. AgroNet harnesses some of the tried-and-tested technologies to effectively provide consultancy and quick assistance to small and mid-level farmers quickly, with an estimated response time between 24 and 48 hours.